How Do Young Professionals in Taiwan Experience Sexual Imagery in Advertising? A ZMET Study. - HUNG, TZECHI (2017)
Sexual appeals have become one communication technique in mainstream consumer advertising. It is suggested that the use of sexual appeals in advertising has become more extreme and suggestive than ever before. While some researchers believed the reason is that companies have witnessed successful patterns in adopting this kind of marketing tactics, other researchers have highlighted the use of sexual appeals in advertising can bring negative effects to the society. This study examines how young professionals in Taiwan experience sexual appeals in advertising and its influence on attitudes toward such advertisements. The ZMET method was utilized in this research as to uncover the deep metaphors of Taiwanese consumer toward the concept of sexual imagery. This study recruited 20 of the Taiwanese people including ten male and ten female participants. The major findings were divided into three perspectives: business perspective, cultural perspectives, and consumer behavior perspective.